A theoretical approach for the description of phenol removal by novel activated carbons - Valente Nabais, Joao (2000)
The adsorption of phenol for the removal of this toxic compound has been investigated in many experimental studies whereas the simulation studies are scarce, especially comparisons with experimental data. This work aims to give deeper insight into the adsorption of phenol using GCMC and MD simulation. Carbon black is used as a reference material and comparison with experimental data for the carbon black and activated carbon data was done.